How Hunter Perceptions of Wildlife Regulations, Agency Trust, and Satisfaction Affect Attitudes about Duck Bag Limits. Issue 5 (3rd September 2017) - Schroeder, Susan A.; Fulton, David C.; Lawrence, Jeffrey S.; Cordts, Steven D.
ABSTRACT: This study explored how factors, including the function of bag limits, agency trust, satisfaction, hunting participation, and demographics, related to opinions about duck bag limits. The results are from a survey of 2014 Minnesota resident waterfowl hunters. Analyses identified four dimensions of attitudes about functions of bag limits, including that they: (a) are descriptive in defining the acceptable number of ducks that can be bagged, (b) are injunctive in establishing how many ducks should be allowed to be bagged, (c) ensure fair opportunities for all hunters to bag ducks, and (d) reflect biological limitations to protect waterfowl populations. Descriptive and fairness functions of bag limits were related to opinions about bag limits, as were factors related to agency trust, satisfaction, ducks bagged, experience with more restrictive bag limits, hunter age, and hunting group membership. Agencies may increase support by building trust and emphasizing the descriptive and fairness functions of regulations.